Winter nutrition for cows - Schalles, R.R.; Drake, C.L.; Kiracofe, G. (Kansas State University. Agricultural Experiment Station, 2011)
Cow productivity on four supplemental winter feeding levels were compared over 2 years. Cattle were grazed on native bluestem year round. Cows calved between February 15 and May 5. Only records (104) of cows that raised a calf in the year considered were used in this report. Cows averaged 3.3 years old at birth of calves. Rations fed are given in Table 25 referred to as group 1, 2, 3 and 4. Cows received the same ration each year. Cows were allotted to 4 groups and rotated among four approximately equal pastures so each group remained in each pasture an equal t:ime. Calves were weighed at birth and cows and calves were weighed each month. During the first year, cows were rectally palpated each week after calving until the first heat to determine time of ovulation and uterine size.
Keywords: Beef; Winter; Bluestem pasture; Nutrition